TIPOLOGI DAN PELESTARIAN BANGUNAN BERSEJARAH; Sebuah Pemahaman melalui Proses Komunikasi - Tri Prasetyo Utomo (Institut Seni Indonesia Surakarta, 2005)
The historic building forms are a facility for communication media in architecture. In architecture, the building forms have mean a sentence for a message and an expression. The building form are form elements, there are door, window, wall, roof, and floor, then to unite with form that a total architecture design. The building form element can’t explain a message if it’s a single building. Whatever, if it are unite, then the elements can become a communication media for to explain a message to observer.Keyword: architecture, building, elemen, communication